Prevalence and association of musculoskeletal disorders among breastfeeding women in Saudi Arabia - Almutairi, Sattam; Aljutaily, Raghad; Alshuwayman, Raghad; Almutairi, Marzouq; Alshehre , Yousef (Journal of the Pakistan Medical Association, 2023)
Objectives: To investigate the prevalence of musculoskeletal disorders, and to explore the association between maternal positioning and musculoskeletal pain among lactating women. Methods: The cross-sectional survey-based study was conducted from January to May 2022 at buraidah, Saudi Arabia, and comprised Arabic-speaking women aged 18-49 years who were breastfeeding. Sociodemographic and clinical data related to musculoskeletal disorders was collected using a redesigned questionnaire through Twitter and WhatsApp platforms. Data was analysed using SPSS 28. Results: Of the 474 women who responded, 192(40.7%) were excluded because they did not meet the eligibility criteria. The sample comprised 281(59.3%) women. The median age was 33 years with an interquartile range of 10 years 71(25.3%). Overall, 163(58%) subjects reported musculoskeletal pain caused by breastfeeding, 78(27.8%) experienced musculoskeletal pain with breastfeeding, 43(15.3%) considered discontinuing breastfeeding, and 59(21%) reported that musculoskeletal pain prevented them from performing their activities of daily living. The most painful segments reported were the back 6.24±3.21, nipple 5.51±3.43, shoulders 4.88±3.40, and neck 4.10±3.13. Sitting on a mat was the commonly adopted maternal positioning 2.38±1.41. Cradle hold was the most convenient baby-holding positioning during breastfeeding reported by 170(60.5%). Conclusion: The prevalence of musculoskeletal disorders was found to be high among breastfeeding women in Saudi Arabia, and an association was found between musculoskeletal disorders and maternal breastfeeding positioning. Key Words: Breastfeeding, Musculoskeletal pain, Physical therapy, Lactation, Women’s health.